SOLTI-1805 TOT-HER3 Study Concept: A Window-of-Opportunity Trial of Patritumab Deruxtecan, a HER3 Directed Antibody Drug Conjugate, in Patients With Early Breast Cancer - Pascual, Tomás; Oliveira, Mafalda; Ciruelos, Eva; Bellet Ezquerra, Meritxell; Saura, Cristina; Gavilá, Joaquin; Pernas, Sonia; Muñoz, Montserrat; Vidal, Maria J.; Margelí Vila, Mireia; Cejalvo, Juan M.; González-Farré, Blanca; et al. (Frontiers in Oncology, 2021)
Abstract Background Preclinical data support a key role for the human epidermal growth factor receptor 3 (HER3) pathway in hormone receptor (HR)–positive breast cancer. Recently, new HER3 directed antibody drug conjugate have shown activity in breast cancer. Given the need to better understand the molecular biology, tumor microenvironment and mechanisms of drug resistance in breast cancer, we designed this window-of-opportunity study with the HER3 directed antibody drug conjugate patritumab deruxtecan (HER3-DXd; U3-1402). Trial design Based on these data, a prospective, multicenter, single-arm, window-of-opportunity study was designated to evaluate the biological effect of patritumab deruxtecan in treatment naïve patients with HR-positive/HER2-negative early breast cancer whose primary tumors are ≥1 cm by ultrasound evaluation. Patients will be enrolled in four cohorts according to the mRNA-based ERBB3 expression by central assessment. The primary endpoint is CelTIL score after one single-dose. A translational research plan is also included to provide biological information and to evaluate secondary and exploratory objectives of the study. Trial registration number: EudraCT 2019-004964-23; NCT number: NCT04610528